Control and placement of intracranial microcatheters. - Kerber, C W; Bank, W O; Manelfe, C (American Journal of Neuroradiology, 1980)
Balloon-tipped microcatheters allow flow-guided entry into small vessels and permit selective angiography, selective drug infusion, temporary or permanent vessel occlusion, and controlled deposition of tissue adhesives. However, active directive techniques are not usually successful with balloon microcatheters, and more passive flow-directed maneuvering must be learned. Three conditions may be encountered. In the first, the vessel to be entered is large and exits at a small angle from the parent vessel. Flow and momentum carry the microcatheter toward the goal. In the second, the abnormal vessel exists at a large angle but is larger than the continuing vessel. Inflating the balloon until it is larger than the continuing vessel will cause the flow to carry it around even sharp bends. In the third, the abnormal vessel is small and also exits at a large angle. Two balloons must then be used. The first occludes the larger mainline continuing vessel, while a second is injected; flow then carries the second around the bend.